Analisis Kemampuan Siswa Kelas IV dalam Menyelesaikan Soal Matematika Model TIMSS di SD se-Gugus III Kecamatan Kedungkandang Kota Malang - Reny Oktaviana; Yulia Linguistika; Erif Ahdhianto; Reny Oktaviana; Yulia Linguistika (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2021)
Abstract: The purpose of this research was to obtain an overview of the achievement of students' abilities in solving mathematics problems using the TIMSS model based on the content domain and cognitive domain. The subjects of this study were fourth grade elementary school students in Cluster III, Kedungkandang District, Malang City as many as 83 students. The type of research used is mixed method research which consists of quantitative research and qualitative research. The average achievement of the content domain scores on the number material 518 (intermediate), measurement and geometry material 456 (low) and data display material 517 (intermediate). While the average achievement of cognitive domain scores in the knowing domain is 593 (high), applying domain is 480 (intermediate) and the reasoning domain is 411 (low). The achievement of the ability of fourth grade elementary school students in Cluster III of Kedungkandang District, Malang City was the most achieved on the low criteria achieved by 32 students, intermediate criteria achieved by 30 students, high criteria achieved by 11 students and advance criteria achieved by 10 students. In general, the average student achievement score of 500 which is included in intermediate criteria. Abstrak: Tujuan dari penelitian ini adalah memperoleh gambaran capaian kemampuan siswa dalam menyelesaikan soal matematika model TIMSS berdasarkan domain konten dan domain kognitif. Subjek penelitian ini yaitu siswa kelas IV SD Se-Gugus III Kecamatan Kedungkandang Kota Malang sebanyak 83 siswa. Jenis penelitian yang digunakan adalah mixed method research yang terdiri dari penelitian kuantitatif dan penelitian kualitatif. Capaian rata-rata skor domain konten pada materi bilangan 518 (kriteria kemampuan sedang), materi pengukuran dan geometri 456 (kriteria kemampuan rendah) dan materi penyajian data 517 (kriteria kemampuan sedang). Sedangkan capaian rata-rata skor domain kognitif pada domain pengetahuan 593 (kriteria kemampuan tinggi), domain penerapan 480 (kriteria kemampuan sedang) dan domain penalaran 411 (kriteria kemampuan rendah). Capaian kemampuan siswa kelas IV SD se-Gugus III Kecamatan Kedungkandang Kota Malang yang paling banyak dicapai pada kriteria kemampuan rendah yang dicapai oleh 32 siswa, kriteria kemampuan sedang dicapai oleh 30 siswa, kriteria kemampuan tinggi dicapai oleh 11 siswa dan kriteria kemampuan sangat tinggi dicapai oleh 10 siswa. Secara umum rata-rata capaian siswa yaitu dengan skor 500 yang termasuk dalam kriteria kemampuan sedang atau intermediate.